SAT0436 Safety and Effectiveness of Adalimumab in Children with Polyarticular Juvenile Idiopathic Arthritis Aged 2 To <4 Years or ≥4 Years Weighing <15 KG. (23rd January 2014) - Kingsbury, D.; Quartier, P.; Arora, V.; Kalabic, J.; Kupper, H.; Mozaffarian, N.
Abstract : Background: Adalimumab (ADA) is approved for use in moderate to severe juvenile idiopathic arthritis (JIA) in patients (pts) ≥4 years (yrs) old in the US, EU, and Japan. Limited data are available in pts <4 yrs old. Objectives: To assess the safety and effectiveness of >1 year of ADA therapy in pts aged 2 to <4 yrs old or ≥4 yrs old weighing <15 kg with moderately to severely active polyarticular JIA. Methods: JIA pts were treated with ADA 24 mg/m 2 (maximum=20 mg/dose) every other week (wk) +/- methotrexate for 96 wks in an ongoing international, multicenter, open-label, phase 3b study until achieving the limit for age (≥4 yrs) and weight (≥15 kg). Adverse events (AEs) were summarized for all visits up to 96 wks. Clinical effectiveness endpoints included American College of Rheumatology pediatric (PedACR) 30/50/70/90 responses through wk 60, and JIA outcome parameters (PhGA, PaGA, DICHAQ, AJC73, LOM69, CRP, TJC, SJC, and POM75). Results: 32 pts were randomized; through wk 60, two pts withdrew due to AEs (JIA worsening or flare) and 2 withdrew for other reasons. AE incidence rates included: any AEs (91%), serious AEs (16%), infectious AEs (78%), and serious infections (9%). No deaths, malignancies, or opportunistic infections were reported. 90% of pts had achieved PedACR30 at wk 60 (Table 1 ). High PedACR 50/70/90 response rates were achieved at wk 24 and maintained through wk 60. Statistically significant improvements in other JIA outcomes were also observed (Table 2 ). Growth was not adversely impacted by ADA treatment; based on CDC growth standards, at baseline, 50%/53% of pts were in the ≥33rd percentile for height and body mass index, respectively; at wk 60, this had increased to 76%/67%. Conclusions: In this very young population with polyarticular JIA, primary clinical trial data revealed that the safety profile and effectiveness of ADA were comparable to that observed in older children with JIA. No adverse effects on growth were observed; however, data did reflect improvement in growth through wk 60 of the study. Acknowledgements: AbbVie Inc funded the study (NCT00775437 ). AbbVie was responsible for the study design, research, analysis, data collection, interpretation of data, and writing, reviewing, and approving of the publication. Medical writing support was provided by Kathleen V. Kastenholz, PharmD, MS, of AbbVie. Disclosure of Interest: D. Kingsbury Grant/research support from: AbbVie, P. Quartier Grant/research support from: AbbVie, Novartis, Pfizer, Consultant for: AbbVie, Novartis, Pfizer, V. Arora Shareholder of: AbbVie, Employee of: AbbVie Inc, J. Kalabic Shareholder of: AbbVie, Employee of: AbbVie Deutschland GmbH & Co. KG, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie Deutschland GmbH & Co. KG, N. Mozaffarian Shareholder of: AbbVie, Employee of: AbbVie Inc